Nutritional Status and Dental Caries in the Perspective of Sustainable Health Promotion - I Gusti Ayu Ari Agung; Ni Putu Idaryati; Gusti Ayu Yohanna Lily; Hervina Hervina; Anak Agung Ngurah Subawa; Patriliani Angeli Sangkur (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2026)
Nutritional status and dental caries are interconnected key indicators of child health and quality of life, reflecting biological determinants. Dental caries remains prevalent among elementary school children and is influenced by nutritional status, sugar intake, and oral hygiene behavior. Nutritional status may influence caries risk by affecting tooth development, salivary composition, and dietary patterns. This study aimed to analyze the relationship between nutritional status and dental caries among children at SDN 21 Dangin Puri, Denpasar. This research used an observational cross-sectional analytical study among 70 students aged 7–12 years. Nutritional status was assessed using BMI-for-age based on WHO standards. Dental caries status was determined using the DMFT/dmft index based on WHO criteria. Results showed 51.4% of students had poor nutritional status, and 28.6% had high caries. Tests showed a significant relationship between nutritional status and caries, p-value <0.05. A significant association exists between nutritional status and dental caries among students. The School Dental Health Program should be optimized through preventive efforts integrating nutrition and policy interventions. A low-sugar diet is effective for preventing dental caries and improving children’s dental health.